2016
DOI: 10.4103/0974-2727.176230
|View full text |Cite
|
Sign up to set email alerts
|

Serum Total Sialic Acid and Highly Sensitive C-reactive Protein: Prognostic Markers for the Diabetic Nephropathy

Abstract: Background:This study was undertaken to evaluate and establish the role of total sialic acid (TSA) and highly sensitive C-reactive protein (hs-CRP) in type 2 diabetes mellitus (T2DM) and its correlation with complications such as diabetic nephropathy.Materials and Methods:One hundred fifty-seven patients with T2DM with nephropathy (DN) and 162 patients of T2DM without nephropathy (DM) along with 165 unrelated age and sex-matched healthy controls were included in the study. Serum glucose (fasting and postprandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
2
19
1
Order By: Relevance
“…In line with our results, previous studies also reported high hsCRP in patients with DN. [ 26 27 ] Furthermore, earlier studies reported the utility of some other parameters such as cystatin C, for estimation of eGFR decline, suggesting its high diagnostic accuracy for screening of DN. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, previous studies also reported high hsCRP in patients with DN. [ 26 27 ] Furthermore, earlier studies reported the utility of some other parameters such as cystatin C, for estimation of eGFR decline, suggesting its high diagnostic accuracy for screening of DN. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Liu et al, [18] confirmed that the levels of hs-CRP are higher in macro-albumiuria than micro-albumiuria and normo-albuminuia groups, and it could be used as an indicator of progression of diabetic nephropathy in diabetes mellitus patients. Moreover, Varma et al, [19] reported that hs-CRP levels were significantly correlated to the fasting blood glucose, two hours post prandial, HbA 1C and urinary microalbuminuria. And they stated that it may increase the microangiopathic complications of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 98%
“…Hs-CRP is an acute-phase index of micro-inflammatory response that can activate the complement system in the body and enhance the leukocyte phagocytosis by binding to the chromatin and can play a regulatory role by stimulating cell activation ( 16 ). Hs-CRP can cause inflammatory response of the body, which is an important pathological process of DN ( 17 ). Previous findings have shown that hs-CRP is an independent risk factor of obesity and type 2 diabetes and hs-CRP is closely related to DN ( 18 ).…”
Section: Discussionmentioning
confidence: 99%